2015
DOI: 10.1614/ws-d-14-00149.1
|View full text |Cite
|
Sign up to set email alerts
|

A Multistate Study of the Association Between Glyphosate Resistance and EPSPS Gene Amplification in Waterhemp (Amaranthus tuberculatus)

Abstract: Waterhemp is an increasingly problematic weed in the U.S. Midwest, having now evolved resistances to herbicides from six different site-of-action groups. Glyphosate-resistant waterhemp in the Midwest is especially concerning given the economic importance of glyphosate in corn and soybean production. Amplification of the target-site gene, 5-enolpyruvylshikimate-3-phosphate synthase (EPSPS) was found to be the mechanism of glyphosate resistance in Palmer amaranth, a species closely related to waterhemp. Here, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
55
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 25 publications
4
55
2
Order By: Relevance
“…This comprised only 9% of the resistant populations studied. These results are consistent with previous findings that gene amplification is associated with glyphosate resistance in multiple geographic locations (Chatham et al 2012(Chatham et al , 2013.…”
Section: Resultssupporting
confidence: 93%
“…This comprised only 9% of the resistant populations studied. These results are consistent with previous findings that gene amplification is associated with glyphosate resistance in multiple geographic locations (Chatham et al 2012(Chatham et al , 2013.…”
Section: Resultssupporting
confidence: 93%
“…The evolution of GR Palmer amaranth in south-central Nebraska provides cause for concern, considering that glyphosate is the most common herbicide used for weed control in GR corn-soybean cropping systems. While GR Palmer amaranth has been reported in west-central Nebraska, the evolution of GR Palmer amaranth in south-central Nebraska will add management challenges for growers because GR common ragweed (Ambrosia artemisiifolia L.), common water- A rapid molecular test, EPSPS gene amplification, has been identified to confirm glyphosate resistance in weeds and has been tested in a Palmer amaranth biotype from Georgia (Gaines et al 2010), populations of waterhemp from Illinois (Chatham et al 2015b), and GR waterhemp populations from several states in the Midwest (Chatham et al 2015a). The molecular test confirmed that the putative GR Palmer amaranth from south-central Nebraska acquired resistance by amplifying the EPSPS gene copy number; however, more research is needed to determine whether other mechanisms of resistance are involved.…”
Section: Palmer Amaranth Biotypesmentioning
confidence: 99%
“…Extensive genetic variability, coupled with intense herbicide selection, resulted in evolution of resistance to several commonly used herbicides, including glyphosate in A. tuberculatus populations throughout the US (Nandula et al, 2013;Chatham et al, 2015a;Lorentz et al, 2014;Bell et al, 2013).…”
mentioning
confidence: 99%
“…For example, target-site resistance to glyphosate as a result of mutations in the EPSPS gene resulting in amino acid substitution at Pro-106 or Thr-102 residues (corresponding to EPSPS sequence in Arabidopsis [Arabidopsis thaliana]) has been documented in glyphosate-resistant (GR) Eleusine indica (Baerson et al, 2002;Powles and Preston, 2006;Kaundun et al, 2008;Yu et al, 2015), L. rigidum (Kaundun et al, 2011;Powles and Preston, 2006;Preston, 2006a, 2006b), and A. tuberculatus (Nandula et al, 2013). On the other hand, EPSPS gene amplification as a mechanism of glyphosate resistance was first reported by Gaines et al (2010) in Amaranthus palmeri, a closely related species of A. tuberculatus, and later was also found in many other weeds, including Kochia scoparia (Wiersma et al, 2015), A. tuberculatus (Lorentz et al, 2014;Chatham et al, 2015a), A. spinosus (Nandula et al, 2013), L. perenne ssp. multiflorum (Salas et al, 2012), E. indica , and Bromus diandrus (Malone et al, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation